2016
DOI: 10.1111/coa.12501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antioxidant effects of melatonin on the larynx mucosa of rats exposed to environmental tobacco smoke

Abstract: The study shows that smoking induces substantial pathological changes in the laryngeal mucosa and melatonin may have some beneficial effects in partially reversing smoking-induced laryngeal injury by inducing the expression of antioxidants; biochemical and histological outcomes also support these findings due to preventing tissue damage in laryngeal mucosa exposed to smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Indoleamine also has a protective effect on other organs such as the thyroid, larynx, kidneys and pancreas (36)(37)(38)(39)(40)(41). Melatonin reduces hyperthyroidism induced by oxidative stress in hamsters and decreases nerve cell death in the region of the hippocampus of the brain.…”
Section: Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Indoleamine also has a protective effect on other organs such as the thyroid, larynx, kidneys and pancreas (36)(37)(38)(39)(40)(41). Melatonin reduces hyperthyroidism induced by oxidative stress in hamsters and decreases nerve cell death in the region of the hippocampus of the brain.…”
Section: Animal Modelmentioning
confidence: 99%
“…Smoking causes pathological changes in the mucous membrane of the larynx and the development of tumors. Studies in rats have shown that melatonin may, to a certain extent, suppress adverse effects, which may be important for smokers (41).…”
Section: Animal Modelmentioning
confidence: 99%
“…MT is likely an effective therapy for minimizing certain adverse consequences of smoking and can be used as a scavenger to counteract the oxidative damage that smoking causes. Moreover, by inhibiting the activation of oxidants and, in turn, stimulating pathways in which antioxidant enzymes are involved, intraperitoneal MT injection decreased oxidative stress damage and mitigated the adverse effects of smoking [28].…”
Section: Discussionmentioning
confidence: 99%
“…We have evaluated and ranked the protective effects of 5 popular, highly commercialized and readily available over the counter (OTC) antioxidants (Coenzyme Q10, Melatonin, Glutathione, Lipoic acid and Resveratrol) to prevent BBB endothelial damage caused by exposure to soluble CSE. Although protective effects of these antioxidants against CS induced injury in different medical conditions have been reported in a few occasions, melatonin, for example has been proven to be a useful against CS induced kidney damage (Ozan, Sonmez, Ozan, Colakoglu, Yilmaz, and Kuloglu, 2007), vasculopathy (Rodella, Filippini, Bonomini, Bresciani, Reiter, and Rezzani, 2010), inflammation of the larynx (Donmez, Yigit, Bilici, Dursun, Gul, Dastan, and Uzun, 2015) and arterial occlusion (Yang, Li, Wang, Liu, Ye, Ni, Zeng, Miao, Wang, and Liu, 2014) while resveratrol and lipoic acid have been shown to have beneficial roles against CS induced pulmonary inflammation (Liu, Ren, Chen, Huang, Li, Zhang, and Wang, 2014) and oxidative damage respectively (Jia, Liu, Sun, Miller, Ames, Cotman, and Liu, 2007). For the first time, our lab is reporting the protective effects of all five of these popular antioxidants against CS induced damage to BBB.…”
Section: Introductionmentioning
confidence: 99%